News treatment of the issue of terrorism on satellite channels: An applied descriptive study on the Qatari Al Jazeera channel in the period from May 2018 - May 2019 - Gadeen, Naglaa Hamdan (Journal of Humanities & Social Sciences, 2024)
The study has examined TV channels'' reporting of terrorist issues as news worthy for mass media and the problems posed in terms of handling Aljazeera News TV Channel was chosen as a case study because it is the sole and the first Arab specialized news TV channel. It has followed bold position in handling all issues and considered the other opinion.The study has adopted descriptive analytical approach to analyze the data collected randomly from Aljazeera's news bulletins over a period of one year.The study has concluded that the channel is concerned with terrorist incidents. The coverage is positive in most cases and the channel employs all modern technology in reporting terrorist issues. The researcher, however, has recommended that the channels should abstain from repetitive and propagandistic style when dealing with terrorist issues. The channel should not drum up the term "terrorism" so as not to serve directly or indirectly any groups or states. Moreover, Channel should not display slogan or name of certain groups so as not associate Islam and distort it.
Keywords: News Treatment; Al Jazeera; Issue; Terrorism